Pineal Gland Volumes in Patients with Alcohol Use Disorder - Gurok, Mehmet Gurkan; Tabara, Muhammed Fatih; Koc, Mustafa; Yildirim, Hanefi; Atmaca, Murad (Springernature, 2025)
AimsThe effects of chronic alcohol consumption on the morphology of the pineal gland are being studied in animals. However, there is almost no literature on changes in the pineal gland due to alcohol use disorder in humans. This study hypothesised that chronic alcohol consumption causes degeneration of the pineal gland, resulting in a reduction in volume.MethodsThis study compared the pineal gland volumes of 15 patients with alcohol use disorder and 17 healthy controls using T1-weighted brain magnetic resonance imaging.ResultsThe volume of the pineal gland was significantly lower in individuals with alcohol use disorder than in healthy controls. As sex and age may influence absolute pineal volume, these factors were controlled for in a general linear model. Following adjustment, the reduction in pineal gland volume remained statistically significant in patients with alcohol use disorder.ConclusionIn conclusion, this study provides the first data on the neuroanatomical basis of the sleep disturbances commonly observed in patients with alcohol use disorder in clinical practice.
Keywords: Alcohol use disorder; Pineal gland; Volumes; Neuroimaging